Collagen peptide modified carboxymethyl cellulose as both antioxidant drug and carrier for drug delivery against retinal ischaemia/reperfusion injury. Issue 10 (20th July 2018) - Mu, Hua; Wang, Yeqing; Wei, Haiying; Lu, Hong; Feng, Zhuolei; Yu, Hongmin; Xing, Yue; Wang, Haijing
Abstract: Oxidative stress can cause injury in retinal endothelial cells. Carboxymethyl cellulose modified with collagen peptide (CMCC) is of a distinct antioxidant capacity and potentially a good drug carrier. In this study, the protective effects of CMCC against H2 O2 ‐induced injury of primary retinal endothelial cells were investigated. In vitro, we demonstrated that CMCC significantly promoted viability of H2 O2 ‐treated cells, efficiently restrained cellular reactive oxygen species (ROS) production and cell apoptosis. Then, the CMCC was employed as both drug and anti‐inflammatory drug carrier for treatment of retinal ischaemia/reperfusion (I/R) in rats. Animals were treated with CMCC or interleukin‐10‐loaded CMCC (IL‐10@CMCC), respectively. In comparisons, the IL‐10@CMCC treatment exhibited superior therapeutic effects, including better restoration of retinal structural thickness and less retinal apoptosis. Also, chemiluminescence demonstrated that transplantation of IL‐10@CMCC markedly reduced the retinal oxidative stress level compared with CMCC alone and potently recovered the activities of typical antioxidant enzymes, SOD and CAT. Therefore, it could be concluded that CMCC provides a promising platform to enhance the drug‐based therapy for I/R‐related retinal injury.